Field Emission Properties of Polymer Graphite Tips Prepared by Membrane Electrochemical Etching - Knápek, Alexandr; Dallaev, Rashid; Burda, Daniel; Sobola, Dinara; Allaham, Mohammad M; Horáček, Miroslav; Kaspar, Pavel; Matějka, Milan; Mousa, Marwan S (Nanomaterials (Basel, Switzerland), 2020)
This paper investigates field emission behavior from the surface of a tip that was prepared from polymer graphite nanocomposites subjected to electrochemical etching. The essence of the tip preparation is to create a membrane of etchant over an electrode metal ring. The graphite rod acts here as an anode and immerses into the membrane filled with alkali etchant. After the etching process, the tip is cleaned and analyzed by Raman spectroscopy, investigating the chemical composition of the tip. The topography information is obtained using the Scanning Electron Microscopy and by Field Emission Microscopy. The evaluation and characterization of field emission behavior is performed at ultra-high vacuum conditions using the Field Emission Microscopy where both the field electron emission pattern projected on the screen and current-voltage characteristics are recorded. The latter is an essential tool that is used both for the imaging of the tip surfaces by electrons that are emitted toward the screen, as well as a tool for measuring current-voltage characteristics that are the input to test field emission orthodoxy.
Keywords: electrochemical etching; polymer graphite tip; field emission microscopy